Ga-doped IZO films obtained by magnetron sputtering as transparent conductors for visible and solar applications. - Solis Cortes, Daniel; Navarrete-Astorga, Elena; Costa-Krämer, José Luis; Salguero-Fernández, Joaquin; Schrebler, Ricardo; Dalchiele, Enrique A.; Ramos-Barrado, José Ramón; Martín-Jiménez, Francisco de Paula (Elselvier, 2019)
C-axis textured thin films of gallium-doped indium zinc oxide (GIZO) with a 2% ratio of Ga/Zn, were obtained via RF-magnetron sputtering with high transparency and electrical conductivity. A Box-Behnken response surface design was used to evaluate the effects of the deposition parameters (In2O3 target power, deposition time, and substrate temperature) on the chemical composition, optical, electrical, and structural properties of the GIZO films. The optical constants and the electrical properties were obtained using optical models. The GIZO stoichiometry, and therefore the In/Zn atomic ratio, affected the crystallinity, crystalline parameters, band gap, and charge carrier mobility of the GIZO films. The charge carrier density was related to the change in the crystalline parameters of the hexagonal structure and the In/Zn atomic ratio. The best electrical conductivity values (1.75×103 Ω−1 cm−1) were obtained for GIZO films with In/Zn ratio ≥1. Several figures of merit (FOM) defined for the visible and solar regions were comparatively used to select the optimal In/Zn atomic ratio that provided the best balance between the conductivity and the transparency. The optimal In/Zn ratio was in a range of 0.85–0.90 for the GIZO films.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/13167
Keywords: Células solares; TCO; GIZO; Figure of merit; Electrical; Optical; Solar properties